2010
DOI: 10.1021/am100030f
|View full text |Cite
|
Sign up to set email alerts
|

A Si−O−C Composite Anode: High Capability and Proposed Mechanism of Lithium Storage Associated with Microstructural Characteristics

Abstract: A blend of phenyl-substituted, branched polysilane, (Ph(2)Si)(0.85)(PhSi)(0.15), and polystyrene (1:1 in weight) has been transformed into a composite material consisting of graphene layers, Si-O-C glasses, and micropores through a pyrolytic polymer-to-ceramic conversion. Several analytical techniques have been employed to characterize the Si-O-C composite material, demonstrating the presence of the three components in its host framework. The Si-O-C composite material performs well in electrochemical operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
161
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(175 citation statements)
references
References 54 publications
12
161
2
Order By: Relevance
“…Within the work of Reinold et al [12], the excellent performance of carbon-rich SiCN materials with outstanding stability and capacities up to 600 mAh g −1 has been demonstrated, including the discussion of the influence of the molecular polymer structure on the resulting ceramic microstructure and in consequence on the electrochemical performance of the material. By means of solid state NMR of lithiated and delithiated SiCN carbon phase was identified as a major lithium storage site [13], this finding being in agreement with the work of Fukui et al on SiOC materials [14]. Within our previous studies, we have also shown that composite anode materials comprised of SiCN/graphite [15] and SiCN/silicon [16] exhibit enhanced electrochemical properties compared to that of pure graphite and silicon, respectively.…”
Section: Introductionsupporting
confidence: 90%
“…Within the work of Reinold et al [12], the excellent performance of carbon-rich SiCN materials with outstanding stability and capacities up to 600 mAh g −1 has been demonstrated, including the discussion of the influence of the molecular polymer structure on the resulting ceramic microstructure and in consequence on the electrochemical performance of the material. By means of solid state NMR of lithiated and delithiated SiCN carbon phase was identified as a major lithium storage site [13], this finding being in agreement with the work of Fukui et al on SiOC materials [14]. Within our previous studies, we have also shown that composite anode materials comprised of SiCN/graphite [15] and SiCN/silicon [16] exhibit enhanced electrochemical properties compared to that of pure graphite and silicon, respectively.…”
Section: Introductionsupporting
confidence: 90%
“…Silicon oxycarbides are ceramic structures with silicon bonded to both oxygen and carbon simultaneously. The structure of SiOC beside the amorphous silicon oxycarbide network -in which Si atoms share bonds with O and C atoms simultaneously-contains an interconnected disordered free carbon phase which accounts for many of their excellent mechanical and electrochemical properties [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. It came out from our previous studies on SiOC and SiCN ceramic materials [32,52] that free carbon content is an important factor determining reversible Li storage capacity and cycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the unique molecular structures, polymerderived silicon oxycarbide (SiCO) has a reversible capacity of $800 mA h g À1 and is considered as a promising anode materials for Li-ion battery [5][6][7][8][9][10][11]. SiCO has been extensively studied over the past years by experiments, and its unique nano-structure is believed to make a significant contribution to the excellent properties [5][6][7]11,12].…”
Section: Introductionmentioning
confidence: 99%